Web-based tools and resources for legal translators: the JudGENTT translation-oriented glossaries for criminal courts translators - Borja Albi, Anabel; García-Izquierdo, Isabel (Onomázein, 2016)
One of the requirements that most obviously characterises the work of translators in highly specialised fields is to have instant access to expert knowledge management systems that enable them to carry out their work with the precision and rigour demanded when working with specialist texts. However, in the field of professional private translation practice we do not yet have sufficiently powerful tools (of the kind available to international organisations) to enable translators to carry out their terminological work in a systematic way, combining the requirements for linguistic information with those for conceptual information and those related to the time pressure to which they are frequently subject in their work. In this paper we reflect on the general features that such expert knowledge management systems for freelance legal translators should possess, and in particular on the terminological resources that they should feature. To this end we present the design and methodology used by the GENTT research group in creating highly specialised glossaries for translators of criminal court procedure documents from four legal systems: Spain, France, the United Kingdom and Germany. These glossaries are part of a broader webbased expert knowledge management system for translators which also encompasses conceptual (legal concepts and procedures) and textual resources (corpus).